Hot or Not?: A Survey Regarding Knowledge and Use of Complementary and Alternative Practices in Speech- Language Pathology. - Marshall, Rebecca Shisler; Basilakos, Alexandra (Contemporary Issues in Communication Science & Disorders)
Purpose: Complementary and alternative medicine (CAM) is becoming increasingly popular in the United States. This trend in health care means that current and future providers, including speech-language pathologists (SLPs), will be encountering more patients who are interested in or are currently using various forms of CAM. An understanding of the current level of knowledge and the attitudes of SLPs regarding CAM can be important in providing education regarding the growing trends in CAM use and research. Recently, there has been a call to include CAM education in the curricula of health care providers (Parkman, 2005). Method: This survey polled a sample of current and future SLPs in the United States about their existing beliefs and opinions regarding CAM use. Results: Survey responses indicated that this sample of current and future SLPs appears to be open to the idea of CAM use, but that more evidence regarding the therapeutic benefits of CAM in speech-language pathology is needed. Conclusion: The results of this study can provide information to direct the integration of CAM education into the curricula of communication sciences and disorders programs or into continuing education programs. Educating graduate clinicians and professionals of the various CAM modalities and use ensures that they will be knowledgeable about clients’ desired approaches to health care.